The role of internal marketing on Tanzania Standard (Newspapers) Limited Performance: A case of Tanzania Standard (Newspapers) Limited (TSN). - Chikira, Mgheni. (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirements for the award of degree of Master's of Business Administration in Corporate Management (MBA-CM) of Mzumbe University